Post a New Question

maths

posted by .

f(x)=ln(e^x-e^-x), x>0

By applying in turn the Composite and Quotient Rules, find derivative and second derivative.

Thanks.

  • maths -

    f '(x) = (e^x + e^-x)/(e^x - e^-x)
    = e^-x(e^(2x) + 1)/(e^-x(e^(2x) - 1)
    = (e^(2x) + 1)/(e^(2x) -1)

    now use the quotient rule to get the second derivative,
    let me know what you got.

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question